Effects of basicity and MgO content on the viscosity of the SiO2-CaO-MgO-9wt%Al2O3 slag system - Gao, Yun-ming; Wang, Shao-bo; Hong, Chuan; Ma, Xiu-juan; Yang, Fu (International journal of minerals, metallurgy and materials, 2014)
The effects of basicity and MgO content on the viscosity of SiO2-CaO-MgO-9wt%Al2O3 slags with basicity from 0.4 to 1.0 and MgO content from 13wt%to 19wt%were investigated using the rotating cylinder method. A correlation between the viscosity and the slag structure was determined by Fourier transform infrared （FTIR） spectroscopy. It is indicated that the complex network structure of the slag melt is depolymerized into simpler network units with increasing basicity or MgO content, resulting in a continuous decrease in viscosity of the slag. The viscosity is strongly dependent on the combined action of basic oxide components in the slag. Under the present experimental conditions, increasing the basicity is found to be more effective than increasing the MgO content in decreasing the viscosity of the slag. At higher temperatures, the increase of basicity or MgO content does not appreciably decrease the viscosity of the slag, as it does at lower tem-peratures. The calculated activation energy of viscous flow is between 154 and 200 kJ＆#183;mol-1, which decreases with an increase in basicity from 0.4 to 1.0 at a fixed MgO content in the range of 13wt%to 19wt%.